Molten shell-activated, high-performance, un-doped Li4SiO4 for high-temperature CO2 capture at low CO2 concentrations - Wang, Ke; Gu, Feng; Clough, Peter T.; Zhao, Youwei; Zhao, Pengfei; Anthony, Edward J. (Elsevier, 2020)
Lithium orthosilicate (Li4SiO4) represents a potential class of high-temperature sorbents for CO2 capture in power plants and sorption enhanced methane reforming to produce H2. However, conventional wisdom suggests that pure Li4SiO4 should have extremely slow sorption kinetics at realistic low CO2 concentrations. Here, we report the opposite result: using a simple and cost-effective glucose-based mild combustion procedure, an unusually efficient and pure form of Li4SiO4 (MC-0.6) was synthesized to achieve a maximum uptake capacity of 35.0 wt% at 580 °C for CO2 concentrations under 15 vol% and maintained this capacity over multiple cycles. The characterization results showed that highly porous nano-agglomerate-like (50–100 nm) morphologies were apparent and ensured a rapid surface-sorption of CO2. In this process, a macroporous nano-sized Li2SiO3 cover on the melt layer of Li2CO3 was identified for the first time. This special structure appeared to accelerate the transportation of CO2 and the diffusion of Li+ and O2− through a molten layer enhancing contact with CO2. Thus, the sample MC-0.6 reduced both the surface-sorption and diffusion kinetics dependence on low CO2 concentrations. Rather than use traditional approaches (controlled morphologies combined with doping), we have demonstrated that the slow kinetics can be overcome simply by a controlled morphologies strategy, which opens up a new direction for the synthesis of high-performance Li4SiO4 sorbents.
Keywords: CO2 capture; Li4SiO4; Power plants